Case Report: Early Distant Metastatic Inflammatory Myofibroblastic Tumor Harboring EML4-ALK Fusion Gene: Study of Two Typical Cases and Review of Literature - Han, Qianqian; He, Xin; Cui, Lijuan; Qiu, Yan; Li, Yuli; Chen, Huijiao; Zhang, Hongying (Frontiers in Medicine, 2022)
Inflammatory myofibroblastic tumour (IMT) is a distinctive neoplasm that frequently arises in the lung and accounts for approximately 1% of lung tumours. Distant metastatic IMT is extremely rare and has been poorly investigated. This analysis was specifically performed to explore the clinicopathological and genetic features of early distant metastatic IMT. Two typical patients with distant metastatic IMTs were selected, which accounted for 1.13% of all diagnosed IMTs in the last 5 years. One patient was a 55-year-old male patient, and the other patient was a 56-year-old female patient. Both primary tumours arose from the lung, and the initial clinical symptoms of the two patients involved coughing. Both of the imaging examinations showed low-density nodular shadows in the lungs with enhancement around the mass. Microscopically, dense arranged tumour cells, prominent cellular atypia and high mitotic activity with atypical form were more prominent in the metastatic lesions than in the primary lesions. All of the primary and metastatic tumours in both cases showed positive ALK immunostaining and ALK rearrangement via fluorescence in situ hybridization. The EML4 (exon 6)-ALK (exon 20) fusion variant (v3a/b) was identified by using next-generation sequencing (NGS) and was verified by using reverse transcription polymerase chain reaction. Furthermore, intronic variants of NOTCH1 and synonymous variants of ARAF were also detected via NGS in one IMT for the first time and were verified in all of the primary and metastatic lesions via polymerase chain reaction. Distant metastasis occurred during a short period of time (one and two months) after the first surgery. One patient presented with multiple metastases to the subcutaneous tissue and bone that responded to ALK inhibitor alectinib therapy, and the tumour was observed to regress 10 months after the initial ALK inhibitor therapy. In contrast, the other patient presented with subcutaneous neck metastasis without ALK inhibitor treatment and succumbed to the disease within 3 months after surgery. This study demonstrated the possible role of EML4-ALK v3a/b in the malignant progression of IMT and proposed certain therapeutic effects of ALK inhibitors on multiple metastatic IMTs.